Osmotic Membrane Bioreactor for Oily Wastewater Treatment using External & Internal Configurations - Al-Alalawy, Ahmed Faiq; Abbas, Talib Rashid; Mohammed, Hadeer Kadhim (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
The present work aims to study the treatment of oily wastewater by means of forward osmosis membrane bioreactor process. Side stream (external) configuration and submerged (internal) configuration of osmotic membrane bioreactor were performed and investigated. The experimental work for each configuration was carried out continuously over 21 days. The flux behavior of forward osmosis membrane in an osmotic membrane bioreactor (OMBR) was investigated, using NaCl as the draw solution and CTA as FO membrane. The effect of mixed liquor suspended solids (MLSS) concentration and TDS accumulation of bioreactor on water ﬂux and membrane fouling behaviors was detected. The accumulation and rejection of nutrients in the bioreactor (Nitrate, COD, and Phosphate) were investigated over the days of the experiment. Water ﬂux and membrane fouling were not signiﬁcantly affected by MLSS concentration at low level and this effect increase with increasing MLSS concentration (4000–10000 mg/L). Besides, water flux was severely affected by elevated salinity of the aeration tank. OMBR showed high removal of COD (96%) and FO membrane revealed high retention of phosphate (97%) but retention for nitrate was relatively low (72%). The sparingly soluble salts in the influent, bioreactor, draw solution, and RO effluent were detected through the experiment. The results showed flux decline with time to about 47% from the initial flux and two osmotic backwashing were applied at day 7 and 14 during the operation and the flux restored approximately 30% of its loss. Side stream and submerged configurations revealed nearly similar response over the experiments while side stream module showed better water flux (7.0 LMH) than submerged (6.1 LMH). The results showed that the concentration of inorganic ions is below the limits that may cause severe scaling.